2020
DOI: 10.1002/eco.2229
|View full text |Cite
|
Sign up to set email alerts
|

An isotopic approach to partition evapotranspiration in a mixed deciduous forest

Abstract: Transpiration (T) is perhaps the largest fluxes of water from the land surface to the atmosphere and is susceptible to changes in climate, land use and vegetation structure. However, predictions of future transpiration fluxes vary widely and are poorly constrained. Stable water isotopes can help expand our understanding of land–atmosphere water fluxes but are limited by a lack of observations and a poor understanding of how the isotopic composition of transpired vapour (δT) varies. Here, we present isotopic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 142 publications
(248 reference statements)
0
2
0
Order By: Relevance
“…At the diurnal timescale, some studies illustrated that T/ET emerged as a normal distribution, which increased from the morning, reached maximum values at noon and then decreased (e.g., Sun et al, 2014). Yet the "U" shape pattern of diurnal T/ET was also discovered by previous studies (e.g., Aron et al, 2020;Hu et al, 2014). In our study, T/ET indicated "U" shape diurnal patterns, especially distinct in autumn (Figure 7h).…”
Section: Underlying Mechanisms Of T/et Variationssupporting
confidence: 88%
See 2 more Smart Citations
“…At the diurnal timescale, some studies illustrated that T/ET emerged as a normal distribution, which increased from the morning, reached maximum values at noon and then decreased (e.g., Sun et al, 2014). Yet the "U" shape pattern of diurnal T/ET was also discovered by previous studies (e.g., Aron et al, 2020;Hu et al, 2014). In our study, T/ET indicated "U" shape diurnal patterns, especially distinct in autumn (Figure 7h).…”
Section: Underlying Mechanisms Of T/et Variationssupporting
confidence: 88%
“…Most previous ET partitioning studies utilize only one of the dualstables isotopes of δ 18 O (i.e., Chen et al, 2022;Dubbert et al, 2013;Sun et al, 2014;Wen et al, 2016) or δ 2 H (i.e., Good et al, 2014), even that a dual stable isotopes approach has been used in some studies (Aron et al, 2020;Han et al, 2022;Lu et al, 2017), the accuracy and F I G U R E 1 1 Percentage contributions (sensitivity analysis) of input parameters to the variations of T/ET in isotopic approach. We further calculated the sensitivity of δ E to input parameters in the Craig-Gordon model (Craig & Gordon, 1965).…”
Section: Uncertainty and Possible Error Source In Et Partitioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, neglecting the contributions of bark and/or foliar water uptake could also lead to an overestimation of the risk of hydraulic failure (Earles et al, 2016; Mayr et al, 2014), and eventually of the risk of mortality, as these alternative water uptake pathways (through the leaves and/or the bark) could contribute to partially alleviate drought stress (Breshears et al, 2008). Obtaining estimates of bark and/or foliar water uptake might not be straightforward for most study sites, but coupling complementary approaches to eddy covariance and/or sapflux measurements, such as online measurements of δ 2 H and δ 18 O or other atmospheric tracers (e.g., COS), could help identify missing sources contributing to water uptake (Aron et al, 2020; Wehr et al, 2017; Yakir & Sternberg, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Among the various approaches mentioned above, the stable water isotope method distinguishes ET based on the concept that E and T have different isotopic compositions. (e.g., Aron et al, 2020;Dubbert et al, 2013Dubbert et al, , 2014Iraheta et al, 2021;Rothfuss et al, 2010;Wang et al, 2010;Williams et al, 2004;Wu et al, 2017;Wu et al, 2021). Soil evaporation is more fractionated in comparison to vegetation transpiration at equal initial isotopic boundary conditions (Rothfuss et al, 2020;Wu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%